2017
DOI: 10.18632/oncotarget.21262
|View full text |Cite
|
Sign up to set email alerts
|

Vemurafenib-resistance via de novo RBM genes mutations and chromosome 5 aberrations is overcome by combined therapy with palbociclib in thyroid carcinoma with BRAFV600E

Abstract: PurposePapillary thyroid carcinoma (PTC) is the most frequent endocrine tumor. BRAFV600E represents the PTC hallmark and is targeted with selective inhibitors (e.g. vemurafenib). Although there have been promising results in clinical trials using these inhibitors, most patients develop resistance and progress. Tumor clonal diversity is proposed as one mechanism underlying drug resistance. Here we have investigated mechanisms of primary and secondary resistance to vemurafenib in BRAFWT/V600E–positive PTC patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 55 publications
4
33
0
Order By: Relevance
“…Moreover, the treatment of thyroid cancer cells with the CDK4/6 inhibitor palbociclib (PD-0332991) induces a consistent antiproliferative effect [76]. In keeping with our results, other groups have confirmed the efficacy of palbociclib in in vitro and in vivo preclinical models of TC, also in combination with a PI3K/mTOR inhibitor to bypass mechanisms of therapy resistance [89][90][91]. On the whole, we are confident that the evidence that cyclin D1 represents TC cell vulnerability may prompt preclinical and clinical studies employing CDK4/6 inhibitors for treatment of TC.…”
Section: Validation Of Noa Targetssupporting
confidence: 87%
“…Moreover, the treatment of thyroid cancer cells with the CDK4/6 inhibitor palbociclib (PD-0332991) induces a consistent antiproliferative effect [76]. In keeping with our results, other groups have confirmed the efficacy of palbociclib in in vitro and in vivo preclinical models of TC, also in combination with a PI3K/mTOR inhibitor to bypass mechanisms of therapy resistance [89][90][91]. On the whole, we are confident that the evidence that cyclin D1 represents TC cell vulnerability may prompt preclinical and clinical studies employing CDK4/6 inhibitors for treatment of TC.…”
Section: Validation Of Noa Targetssupporting
confidence: 87%
“…Interestingly, we have shown that activation of AKT in resistant cell lines might be connected with acquired mutations in a gene encoding RBMX, an RNA-binding protein protecting cells against DNA damage and acting as a tumor suppressor [92,93]. Mutations in RBMX were recently reported in papillary thyroid carcinoma cells resistant to vemurafenib [94], and knock-down of wild-type RBMX caused an increase of p-AKT protein level in naïve cancer cells. Several de novo mutations (G379R, Y357H, R339G, S337N, S303 frameshift) in RBMX that span the RNA-interacting domain of RBMX [92] were found in our study, but only one of them S303fs+/− was present in resistant melanoma cell lines with elevated activity of AKT (21_TRAR, 28_TRAR, 29_PLXR).…”
Section: Discussionmentioning
confidence: 97%
“…Additional tools to identify resistant subclones, imply their analysis in cellular systems, which also allows the testing for different and possible novel therapeutic options. As far as TC concerns, Antonello et al expanded a sub-population of cells with primary resistance to vemurafenib and found that they harbor amplification of chromosome 5 and mutations in RBM genes which are crucial for genome stability during cell division [78]. A combined therapeutic approach using BRAF V600E and CDK4/6 inhibitors was able to induce apoptosis in both naïve and vemurafenib-resistant cells, indicating that this combined therapy could be tested in a clinical trial of advanced TC patients.…”
Section: Temporal Heterogeneitymentioning
confidence: 99%